Latino Immigrant Narratives from Maryland - Hernandez-Fujigaki, Jorge (European Scientific Journal, ESJ, 2017)
Despite the intensive work conducted by scholars to capture and preserve the memories of Latino immigrants in the Los Angeles, New York, Miami, and Chicago metro areas, relatively little is known about the history and experiences of this immigrant group living in the Washington metro area, home to twelve of the top sixty Latino communities in the nation.62 Currently, there are 906,000 Latinos living in the region.63 This paper showcases some of the perspectives of Latino immigrants through oral history interviews conducted by students in two undergraduate history courses offer at Montgomery College (MC)64 : â€œHistory of Latinos in the USâ€ and â€œLatin American History.â€ Students in these classes are required to identify immigrant community members and to request their cooperation for being interviewed. The process of collecting, creating, and preserving the life stories of these immigrants stimulates a keen interest in how both place of origin and historical experience inform the lives of immigrants. It gives the students too the opportunity to understand the impact of the past on immigrant experience and to gain an understanding of immigrantsâ€™ aspirations, hopes, and fears as well as their positive contributions to American society and culture. During the course of a semester, students conduct, transcribe, and construct oral histories and compose brief, one-page reflections on their interviews. Specifically, students document how their assumptions about the historical immigrant experience have changed as a result of their participation in this oral history project. The transcripts generated by these students represent original and relevant primary sources contributing an understanding of how the past is prologue for American immigrants going forward and foster an appreciation of the immigrant presence among us.